Factors associated with the outcomes of ANCA-associated glomerulonephritis: a retrospective cohort study - Nikolay M. Bulanov; Ekaterina A. Tao; Ekaterina S. Stoliarevich; Mayra L. Bulanova; Mariia A. Litvinova; Alexey V. Skvortsov; Valeria A. Kokhanchuk; Pavel I. Novikov; Agunda M. Kuchieva; Tatyana S. Kadorkina; Mariia P. Vasilyeva; Sergey V. Moiseev (Терапевтический архив)
Background. Kidney involvement is one of the prognostically significant manifestations of ANCA-associated vasculitis (AAV). The aim of the study was to evaluate factors associated with kidney survival in patients with biopsy proven ANCA-associated glomerulonephritis (ANCA-GN).